Penerapan Aplikasi SIPERDIT di Desa Tegalrandu Kecamatan Klakah Kabupaten Lumajang pada Masa Pandemi COVID-19 - Ahmad Faisol; Sidik Noertjahjono; Mochammad Ibrahim Ashari; Sutanto Hidayat (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2021)
Tegalrandu Village is one of the tourism villages in Klakah sub-district, Lumajang Regency which is famous for its Ranu Klakah lake. The life of the residents of Tegalrandu village, Klakah sub-district, Lumajang district, is quite advanced where almost every villager can access the internet, but this is not in line with village government services that are still provided offline or manually. This is quite risky to do during the COVID-19 pandemic because it has the potential to cause gathering activities. To reduce the risk of COVID-19 transmission, a new computerized system is needed so that it can be accessed online so as to speed up the administrative process and service of letter requests for villagers. This system is called SIPERDIT and is part of the OPENSID application with the addition of several new features. The program method in this activity consists of 2 stages, namely planning and implementing training. The results achieved were website-based applications and mobile Android which were easy to operate because of their user-friendly appearance. After this application was completed, the service team conducted training for users in Tegalrandu village to improve the services for community members.DOI: https://doi.org/10.26905/abdimas.v6i1.4801